Pengembangan Media Pembelajaran Topi Tawa (Tanya Jawab) Berorientasi pada Keterampilan Berpikir Tingkat Tinggi Peserta Didik Kelas V di SDN Panunggulan 2 - Wulandari, Sindy; Hakim, Zerri Rahman; Pribadi, Reksa Adya (Universitas Muhammadiyah Magelang, 2024)
This research aims to develop a laughing hat learning media (question and answer) in the fifth grade science (Natural Science) subject at Elementary School, to determine the feasibility of the laughing hat media and to find out students' responses after carrying out the learning process using the laughing hat media. This research uses the Research and Development (R&D) method using a design model (4D) which includes 4 stages Define–Design–Develop–Desiminate developed by Triagarajan. Data collection techniques in this research used interviews for needs analysis, documrgu entation studies, and product feasibility validation questionnaires for teams of media experts and material experts, as well as response questionnaires for fifth grade elementary school students. The subjects in this research were class V students at SDN Panunggulan 2, totaling 23 students. The results of the product validation test, from media experts obtained an overall average presentation score of 86% with very valid (very feasible) criteria, material expert validation obtained an overall average percentage score of 89% with very valid (very feasible) criteria. So the overall product feasibility presentation reached 88% with very good criteria. Based on the results of research and development carried out by researchers, it was concluded that the laughing hat media (question and answer) in the science subject (Natural Science) material CHAPTER 2 (Harmony in Ecosystems) Topic A.1 Food Chain in class V elementary school (feasible ) and is very good for use in learning activities.